Knowledge management as a strategic asset : an integrated, historical approach - Johannessen, Jon-Arild (Emerald points., 2018)
Since it was established as a discipline in 1991, knowledge management has contributed significantly to our understanding of how firms can achieve competitive advantage. To build a foundation for competitive advantage, however, a company must first consider knowledge management as a strategic asset. It must truly grasp how knowledge management can be utilized to build the future of the company. Here Jon-Arild Johannessen examines the history of knowledge management in order to highlight the contributions that the discipline can make to twenty-first-century strategic challenges. Through a series of case studies, Johannessen delves into the relations between knowledge management, organizational learning, innovation, and internal training in order to show how they can help firms gain sustainable competitive advantage. Using systemic thinking, a new way of looking at knowledge management, Johannessen focuses on how organizations can use their data to think about how to create their own futures rather than simply to adapt to what others have createdhow they can go beyond red ocean and even blue ocean theories in order to create their own oceans of possibility.For the new perspective it offers on the biggest contemporary strategic challenges in business, Knowledge Management as a Strategic Asset is essential reading for managers, researchers, and anyone interested in the cutting edge of strategic thinking.